Kinerja Birokrasi dalam Mempersiapkan Bahan Administrasi Pembuatan Daftar Urut Kepangkatan dan Analisis Jabatan Sekretariat DPRK Langsa - Chairul Fahmi; Budi Hartono; Maksum Syahri Lubis (Mahesa Research Center, 2023)
This study aims to identify and analyze the performance of the bureaucracy in preparing administrative materials for making rank order lists and position analysis for the Langsa City DPR Secretariat and to find out the factors that support and hinder bureaucratic performance in preparing administrative materials for making rank order lists and position analysis for the Langsa City DPR Secretariat. The method used is a qualitative method with an inductive approach. Data collection techniques include interviews, observations, and documentation. This research was conducted at the Langsa DPRK Secretariat Office from October 2022 – September 2022. This research used the method of data collection, data reduction, data presentation, and drawing conclusions. The results of the study revealed that there were 5 stages in knowing the performance of the bureaucracy in preparing administrative materials for making rank order lists and analysis of program and financial positions of the DPRK Langsa Secretariat consisting of (1) Productivity found a discrepancy between the position map structure of the DPRK Langsa Secretariat and Job Analysis and Workload Analysis, (2) Responsiveness found the position analysis document of the DPRK Langsa Secretariat last made in 2018 which was not in accordance with the Organizational Structure, (3) Service Quality found that there were no problems and was counted well, (4) Responsibility found that the head of the General Administration Subdivision and Personnel do not know the main tasks and functions of the position before taking office and after taking office, (5) Accountability is known in the General Administration and Personnel Sub-Division that has not been able to meet accountability criteria such as being result-oriented and improving work.